"Click Synthesis" of Mercaptosilyl-Functionalized Ionic Liquids via Thiol-Ene Chemistry for Use as Hydrophobic Surface Coating Agents. (30th August 2016) - Sanchez Zayas, Manuel; Nestor, Stephen; Gaitor, Jamie; Reardon, Melissa; Mirjafari, Arsalan
Abstract : The thiol-ene "click" transformation described here is a high-yielding and simple fusion process, leading to a series of hydrophobic, multifunctionalized ionic liquids containing long thioether spacers (C7, C11 and C15 ) with low melting points and high thermal stability. The process exhibits broad scope and provides a series of imidazolium-based mercaptosilyl-functionalized ionic liquids in excellent yields and exclusive anti-Markovnikov regioselectivity. The synthesized ionic liquids were found to be active surface coating agents and were successfully immobilized on magnetite supermagnetic Fe3 O4 nanoparticles. The representative ionic liquids with different side chains were immobilized on the surface of Fe3 O4 magnetic nanoparticles and showed high organic loading and low size of nanoparticles.